A Study of Aged Persons at Chennai’s Old Age Homes in Terms of Sociology of Health: Examining the Needs and Rights of Elderly People in Chennai's Old Age Homes (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Government initiatives to eliminate abuse of senior adults are fast rising in the fields of modern, social, economic, public interest, and other aspects. However, the attitude toward elderly people is changing people have begun to despise them, and they have been forced to leave their houses. As a result, people become homeless and may be forced to relocate into old age facilities. The needs of senior folks are the subject of this essay. This article will be taken from a Delhi-based old age home that works to safeguard the rights of elderly people in order to emphasise the importance of research.